Are We on the Right Track?: Overview of Unregistered Drugs in Malaysia - Zulkifli, Nur Wahida; Abd. Aziz, Noorizan; Hassan, Yahaya; Azmi Hassali, Mohamed; Zainal Bahrin, Nur Liyana; Ahmad, Azlan (Journal of Pharmacy Practice and Community Medicine)
Background: The Ministry of Health (MOH) under their sub-division, the Pharmacy Enforcement Division (PED) has a crucial role in managing unregistered drugs in Malaysia market. The unregistered drug is like a silence killer in the pharmaceutical industry. It does damage not only the pharmaceutical economy but also the consumers’ health. PED aims are to ensure that every pharmaceutical, traditional and cosmetic are quality, safe and efficient to be used meaning they need to be registered and notify. However, the problem of unregistered drugs still remains and this needs to be worried. Objective: This paper aims to get the overview of the seriousness of this issue, the current management and the impact on the consumers and nation. Conclusion: Therefore, with the cumulative evidence from this paper can provide the vision or suggestions what is the need to be done in combating unregistered drugs for the future in Malaysia.
Keywords: Unregistered drugs; Pharmacy Enforcement Division; Ministry of Health; Malaysia; Counterfeit drugs